G194(P) The availability of laboratory investigations for paediatric inflammatory bowel disease; findings of a nationwide survey. (24th May 2017) - Bates, L; Paul, S; Basude, D
Abstract : Aim: To investigate the availability of IBD related laboratory investigations in NHS laboratories in England and to discern whether there are regional variations. Subjects and Methods: A structured telephone survey was conducted in July 2016 by a single interviewer by contacting the clinical Laboratories in Acute NHS trusts across England with paediatric services. The available online handbooks for each lab were also accessed and where appropriate scientists were unavailable, the survey questions were sent by email. The data was collected on a database and analysed using Microsoft excel. No ethical approval was required for this study. Results: Response was obtained from 136 out of 139 laboratories (97.8%). 1) Inflammatory markers (other than CRP): ESR is widely available at 98%, followed by Plasma viscosity (PV) at 71% and Orosomucoid (ORM) at 48%. Regional variations are significant with East of England and London having least access to PV and ORM 2) Faecal calprotectin was available in 89% of labs although only 51% offer in house testing. 84% allow any clinician to request the test whereas the rest allow only a few clinician groups to request 3) ANCA can be tested in 94% of labs but ASCA is available only in 29% 4) TPMT activity was available in 96% of labs with only 29% testing this on site 5) 6-Thioguanine metabolites was offered only by 58% of labs with 89% outsourcing it. This was most widely accessible in the south east. 6) Infliximab serology is offered in only 61% of labs with only 14% able to test this on site. This is least accessible in the East Midlands. Summary and conclusion: There is extensive regional heterogeneity in the availability of laboratory investigations for PIBD in England with low levels of on site testing. More research is needed to confirm the utility of the laboratory investigations in PIBD and establish their use. National guidelines should include standards for the investigations required and provide information on cost effectiveness to allow Paediatric units in all regions to access the investigations promptly to maintain equal standards of health care for PIBD accross England.